Odpisy statutów cysterskiej kapituły generalnej z XIII i XIV wieku w polskich zbiorach pocysterskich. Wstępna analiza wybranych rękopisów .......... 101 - Galar, Anna (Dzieje i kultura Cystersów w Polsce, 2025)
COPIES OF THE STATUTES OF THE CISTERCIAN GENERAL CHAPTER FROM THE 13TH AND 14TH CENTURIES IN POLISH POST-CISTERCIAN COLLECTIONS: PRELIMINARY ANALYSIS OF SELECTED MANUSCRIPTSCistercian abbots who participated in the annual meetings of the general chapter in Cîteaux were obliged to take home a copy of the statutes – records of the decisions made by the Cistercian general chapter, which formed the base of the Cistercian law. Despite this rule, the medieval legislation of the Cistercian general chapter that is known today is far from being complete. Especially for the 14th century, the number of identified statutes is scarce, which the edition Statuta capitulorum generalium ordinis cisterciensis ab anno 1116 ad annum 1786 published by J.-M. Canivez (1933-1941) has disclosed. However, further research may lead to new discoveries of ‘local collections’ of Cistercian statutes. The aim of the present study is to examine five manuscripts from Cistercian abbeys in Poland and Silesia (Przemęt – Poznań Univeristy Library, rkps 1616; Lubiąż – Wrocław University Library, IV Q 179, IV F 207; Krzeszów – Wrocław University Library, Akc. 1994/56, Akc. 1994/57) which contain the short series of annual Cistercian statutes from 13th and 14th centuries. These manuscripts have not yet been a subject of systematic study. They remain a unique testimony of the Cistercians’ knowledge of law and the relations between the Polish and Silesian Cistercian abbeys and the general chapter in Cîteaux.